Penegakan Hukum terhadap Peredaran Tindak Pidana Narkotika di Wilayah Hukum Polsek Kateman - Agus Saputra Siahaan; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Indragiri Law Review, 2025)
This study aims to analyze law enforcement against narcotics trafficking within the jurisdiction of the Kateman Sector Police and to identify the obstacles encountered during its implementation. The research employed an empirical legal method with a descriptive-analytical approach, combining normative and empirical juridical perspectives. Data were collected through interviews, observations, and literature reviews, and subsequently analyzed qualitatively using a deductive method. The findings indicate that law enforcement has been implemented in accordance with the Indonesian Criminal Procedure Code and Law Number 35 of 2009 concerning Narcotics, covering investigation, inquiry, arrest, seizure of evidence, and case submission to the public prosecutor. The main obstacles include limited personnel, inadequate facilities and infrastructure, challenging geographical conditions, increasingly sophisticated criminal methods, and low public participation in reporting narcotics-related crimes. Therefore, strengthening human resources, improving operational facilities, and enhancing cooperation among the police, government, and the community are essential to achieve effective law enforcement in combating narcotics trafficking